Penerapan Teknologi Skimming dan Bioremediation pada Instalasi Pengelolaan Air Limbah di PT. Waruna Shipyard Indonesia - Siregar, Munawar Alfansury; Damanik, Wawan Septiawan; Lubis, Sudirman; Nasutioon, Arya Rudi; Arif, Arfian (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Water pollution causes environmental damage and is very detrimental to living things. This activity aims to improve the performance of the Wastewater Management Installation (WWTP) which functions to reduce pollutant levels in the waters. Through the collaboration of the UMSU Faculty of Engineering with PT. Waruna Shipyrad Indonesia (WSI), collaboration was also carried out to improve the performance of the wastewater management system. Wastewater management methods are carried out by applying skimming machine technology, and several sensors for the physical properties and composition of water, as well as using remediation of good bacteria from the laboratory. 6 WWTP ponds were implemented, each with dimensions of 3.7x2.8x2.17 m. The skimming machine is designed to use a drum, and the bacteria from the remediation process will suppress the growth of bacteria that damage the environment. The volume of water entering the reservoir is around 207,200 kg/m3 perweek or 207.2 Liters/week. The results of applying this technology obtained an average amount of oil taken every 2 days reaching 600 mL. The average water quality is 6-8 with a pH standard of 6-9, a COD value of 47.8 mg/L with a quality standard of 100 mg/L, and a BOD value of 21.1 mg/L with a quality standard of 30 mg/L.